Role of microRNA-126 in vascular cognitive impairment in mice. Issue 12 (December 2019) - Yu, Peng; Venkat, Poornima; Chopp, Michael; Zacharek, Alex; Shen, Yi; Ning, Ruizhuo; Liang, Linlin; Li, Wei; Zhang, Li; Landschoot-Ward, Julie; Jiang, RongCai; Chen, Jieli
Vascular dementia (VaD) affects cognition and memory. MicroRNA-126 (miR-126) is an angiogenic microRNA that regulates vascular function. In this study, we employ a multiple microinfarction (MMI) model to induce VaD in mice, and investigate VaD-induced cognitive dysfunction, white matter (WM) damage, glymphatic dysfunction and the role of miR-126 in mediating these effects. Male six-to eight-months old C57/BL6 mice (WT) were subject to MMI model, and cerebral blood flow (CBF), vessel patency, glymphatic function, cognitive function, and serum miR-126 expression were measured. Mice were sacrificed at 28 days after MMI. To investigate the role of miR-126 in VaD, cognitive function, water channel integrity and glymphatic function were assessed in male, six-to eight months old conditional-knockout endothelial cell miR-126 (miR-126 EC−/− ), and control (miR-126 fl/fl ) mice. MMI in WT mice induces significant cognitive deficits, decreases CBF and vessel patency; evokes astrocytic and microglial activation, increases inflammation, axonal/WM damage; decreases synaptic plasticity and dendritic spine density, instigates water channel and glymphatic dysfunction, and decreases serum miR-126 expression. MiR-126 EC−/− mice exhibit significant cognitive impairment, decreased CBF, myelin density and axon density, increased inflammation, and significant water channel and glymphatic dysfunction compared to miR-126 fl/fl mice. Reduction of endothelial miR-126 expression may mediate cognitive impairment in MMI-induced VaD.